Delayed Diagnosis and Multi-TKI Intolerance: A Case Report of CML Concurrent With COVID-19 - Luan, Chengxin; Wang, Haixia; Zhou, Junjie; Ma, Xiaoyu; Long, Zhangbiao; Cheng, Xin; Chen, Xiaowen; Xia, Ruixiang; Ge, Jian (Frontiers in Oncology, 2022)
Introduction The hematological manifestations of corona virus disease 2019 (COVID-19) can confound the diagnosis and therapy of other diseases. In this paper, we firstly reported a case of chronic myeloid leukemia (CML) of delayed diagnosis and intolerance to tyrosine kinase inhibitors (TKIs) concurrent with COVID-19. Case Presentation A 56-year-old female was diagnosed as COVID-19 with no obvious leukocytosis [white blood cell (WBC), ≤17 × 109/L] or splenomegaly until ablation of the virus. Bone marrow aspiration was conducted to establish the diagnosis of CML. She accepted an adjusted dosage of imatinib initially and had to suspend it after myelosuppression (day 41). After hematopoietic therapy, imatinib was given again (day 62), but she was still non-tolerant, and nilotinib at 150 mg twice a day was prescribed from day 214. At just about 4 weeks later, nilotinib was discontinued due to myelosuppression. Then, it was reduced to 150 mg per day and was re-initiated (day 349), but she was still non-tolerant to it. Similarly, from day 398, flumatinib at 200 mg per day was tried, but she was non-tolerant. Her white blood cell or platelet count fluctuated markedly with poor therapeutic response. Considering that she was relatively tolerant and responsive to imatinib, the medication was re-initiated at 200 mg and reduced to 100 mg per day. Her follow-up revealed stable WBC and PLT counts. The latest BCR-ABL-210/ABL was decreased to 0.68% at about 6 months after imatinib was re-initiated, which means an improved response. Conclusion The offset effect between CML and SARS-CoV-2 infection was supposed to be the underlying mechanism for the absence of leukocytosis or splenomegaly. The impact of immune network by SARS-CoV-2 preserved and disrupted the patient’s response to TKIs despite the virus’ ablation. We suggest that a continued elevation of basophils may be a useful indicator for CML concurrent with COVID-19, and individualized treatment with adjusted dosage and suitable type of TKIs should be considered to improve the patient’s health outcome.